Tanfîdz Al-Mubârazah at-Tamtsîliyyah li al-Fariq li Ta’lîm Mâddah an-Nahwiy - Ramli, Lalu Abdul Aziz; Muassomah, Muassomah; Anwar, M Syahrul; Norazizah, Siti; Siregar, Amy Fitriani (Jurnal Internasional Pendidikan Bahasa Arab, 2023)
The progress of education in a country is influenced by the quality of teachers and needs to be more creative and innovative in choosing appropriate teaching methods so that the quality of student learning outcomes can be improved. The purpose of this study was to determine the quality of the implementation of student learning outcomes using the cooperative learning team games tournament method and its advantages and disadvantages. This study used a qualitative descriptive analysis method, with data collection techniques using observation and interviews. The results of the analysis carried out by the researcher after the implementation of the team representative duels, there is an ideal increase in the quality of educational outcomes, which proves that this model has a positive effect on student education, and can be observed in terms of participation, interaction, discussion and competition. In general, students like to apply this model because they considered was useful and fun. It was concluded that team games tournament is a model that provides opportunities for students to be more active, answer questions, share opinions and increase student activity in teaching so that the quality of learning outcomes can increase.